Metastasis of Prostate Adenocarcinoma to the Testis - Campara, Zoran (Med Arch, 2016)
INTRODUCTION: Prostate carcinoma is the most frequently diagnosed carcinoma in the male population. The most typical places of the metastases are pelvic lymphatic glands, bones and lungs, and very rarely it metastasizes into a testis. The prognostic importance of testicular metastasis of prostate cancer is not yet well-known, due to a very few published cases. According to the known facts, it is certain that a metastasis of the prostate carcinoma into a testis is a sign of an advanced disease. CASE REPORT: This work presents a 48-year-old patient, to whom an adenocarcinoma of the prostate has been proven by the pathohistological finding of transrectal biopsy, performed due to the elevated level of prostate-specific antigen (PSA). Nine years after the initial diagnosis, due to a gradual rise of PSA and tumorous enlargement of the left testis, left inguinal orchectomy and right orchectomy were performed. Metastatic dissemination of prostate adenocarcinoma into a testis was determined by a pathohistological analysis of the left testis. CONCLUSION: The metastasis of the prostate carcinoma into a testis, as a rare localization of the metastatic dissemination, after additionally performed orchectomy along with further oncological therapy, can provide a continuation of a good life quality as well as a control of the disease in a longer time period.